Identification and characterization of CircRNAs involved in the regulation of wheat root length - Yanhua Xu; Yongzhe Ren; Tongbao Lin; Dangqun Cui (Biological Research, 2019)
Abstract Background Recent studies indicate that circular RNAs (circRNAs) may play important roles in the regulation of plant growth and development. Plant roots are the main organs of nutrient and water uptake. However, whether circRNAs involved in the regulation of plant root growth remains to be elucidated. Methods LH9, XN979 and YN29 are three Chinese wheat varieties with contrasting root lengths. Here, the root circRNA expression profiles of LH9, XN979 and YN29 were examined by using high-throughput sequencing technology. Results Thirty-three and twenty-two differentially expressed circRNAs (DECs) were identified in the YN29-LH9 comparison and YN29-XN979 comparison, respectively. Among them, ten DECs coexisted in both comparisons. As the roots of both LH9 and XN979 were significantly larger and deeper than YN29, the ten DECs coexisting in the two comparisons were highly likely to be involved in the regulation of wheat root length. Moreover, three of the ten DECs have potential miRNA binding sites. Real-time PCR analysis showed that the expression levels of the potential binding miRNAs exhibited significant differences between the long root plants and the short root plants. Conclusions The expression levels of some circRNAs exhibited significant differences in wheat varieties with contrasting root phenotypes. Ten DECs involved in the regulation of wheat root length were successfully identified in which three of them have potential miRNAs binding sites. The expression levels of putative circRNA-binding miRNAs were correlated with their corresponding circRNAs. Our results provide new clues for studying the potential roles of circRNAs in the regulation of wheat root length.